2013
DOI: 10.1021/bi4000854
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Marine Sponge Cyclic Peptide Theonellamide A and Sterols in Lipid Bilayers As Viewed by Surface Plasmon Resonance and Solid-State 2H Nuclear Magnetic Resonance

Abstract: Theonellamides (TNMs) are members of a distinctive family of antifungal and cytotoxic bicyclic dodecapeptides isolated from the marine sponge Theonella sp. Recently, it has been shown that TNMs recognize 3β-hydroxysterol-containing membranes, induce glucan overproduction, and damage cellular membranes. However, to date, the detailed mode of sterol binding at a molecular level has not been determined. In this study, to gain insight into the mechanism of sterol recognition of TNM in lipid bilayers, surface plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…We reported that TNM-BF recognizes 3β-hydroxysterols; the affinity was not affected by the degree of unsaturation in the ring B of sterols [12]. In addition, recently, a non-labeled natural product TNM-A was shown to bind to liposomes containing 10 mol% ergosterol or cholesterol [13]. These results prompted us to test whether fTNMs could recognize membrane sterols in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…We reported that TNM-BF recognizes 3β-hydroxysterols; the affinity was not affected by the degree of unsaturation in the ring B of sterols [12]. In addition, recently, a non-labeled natural product TNM-A was shown to bind to liposomes containing 10 mol% ergosterol or cholesterol [13]. These results prompted us to test whether fTNMs could recognize membrane sterols in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results revealed that the mechanism of membrane binding of 5aTHQ-9n (5)i sd ifferent from that of ergosterol-binding antifungals such as amphotericin B [23] and theonellamides, [24] and of heronamides,s aturated hydrocarbon chain-targeting antifungals. [22,26] Furthermore,h eronamides favor 1,2-dimyristoyl-sn-glycero-3-phosphorylcholine (DMPC) membranes over POPC or 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) membranes. [22,26] Furthermore,h eronamides favor 1,2-dimyristoyl-sn-glycero-3-phosphorylcholine (DMPC) membranes over POPC or 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) membranes.…”
Section: Resultsmentioning
confidence: 99%
“…However, direct interaction between TNMs and sterols in lipid bilayers had not been demonstrated. To address this need, we carried out SS 2 H NMR measurements using TNM‐A in POPC membranes containing chol, ergosterol, or 3‐ epi ‐cholesterol (Figure ) . The 2 H NMR spectra showed that TNM‐A significantly inhibits the fast rotational motion of chol and ergosterol but not 3‐ epi ‐cholesterol, thus confirming the direct intermolecular interaction between TNM‐A and 3β‐hydroxysterols in lipid bilayers.…”
Section: Membrane‐active Natural Products and Their Interactions Withmentioning
confidence: 92%